Radiation therapy students' perceptions of a wiki. (26th September 2017) - Dungey, Gay; Gallagher, Peter
Summary: Background: This pilot study aimed to gain the perceptions of first‐year students using a wiki as a learning tool for the Bachelor of Radiation Therapy degree in New Zealand. Literature suggests that wikis have great potential as an educational tool for both lecturers and students, because they encourage collaborative learning and resource sharing. In 2015, the 'Otago Wiki' platform was introduced as a part of the degree. Methods: The first‐year students were allocated into groups of four. Using the 'Otago Wiki' tool, each group created their own wiki page by addressing assigned tasks over the course of the year that related to a fictional patient. At the end of the year they were invited to participate in an online Survey Monkey ™ questionnaire, which 15/26 students completed. We used a conventional approach to code the free‐text responses for our content analysis. Results: Three main themes emerged from the qualitative data: group work experience; developing a greater self‐awareness of radiation therapy; and improving the learning experience. Although there is room for improvement, the quantitative data indicate that most students found the wiki to be a valuable group exercise, helping them to understand the patient experience. Conclusion: Overall, the students' perceptions of the wiki as a learning tool indicated that it was a worthwhile experience. Moving forward, wikis will continue to be used and incorporated into other modules in the first year. Setting clearer goals for each task would enable the students to use their time more efficiently in the future. Literature suggests that wikis have great potential as an educational tool for both lecturers and students